Previous Crop Impacts on Wheat Variety Performance in Central Kansas During the 2021–2022 Growing Season - L. Simão; A. Patrignani; J. Grané; L. Pradella; N. Giordano; J. A. Romero Soler; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2023)
The effect of a previous crop and its residue left on the field before the next crop is a consequence of soil water usage and residue quality. We evaluated the grain yield of forty winter wheat varieties, as well as soil bulk density, soil water content, and previous crop’s residue C:N ratio in three neighboring fields near Solomon, KS. Wherein these three fields, winter wheat was no-tilled following a previous crop of either 1) soybean; 2) cover crop mix (legume and cereal); or 3) winter wheat. The mix of cover crops consisted of pearl millet, sorghum sudan, and sunn hemp. Soil samples were taken in October during winter wheat sowing. Four replications of soil measurements for bulk density and water content were taken from the 0- to 16-in. depth at 8-in. intervals. Six replications of 10.8-ft2 quadrats of residue biomass were sampled and evaluated for total nitrogen (N) and carbon (C). There were no significant differences in winter wheat grain yield among the varieties nor among the sites, although yield following soybeans was slightly lower than yield following wheat or cover crops (41 vs. 46 bu/a). Soil bulk density and residue C:N ratio were the lowest when following soybean (i.e., greater soil porosity and faster residue decay), although soil water content was also the lowest. Soil water content at sowing was the greatest when following winter wheat, likely as there were no actively growing summer crops to use precipitation water prior to wheat sowing. Soil water content increased at deeper layers (0–8 in. compared to 8–16 in.) when winter wheat was sown following a cover crop mix or a previous winter wheat crop, but it decreased when following soybean. Preliminary results from this on-farm experiment suggest that winter wheat variety performance was similar across previous crops despite measured differences in residue and soil characteristics. These results may help farmers to decide the benefits of each crop residue based on their cropping system needs.
Keywords: cropping system; cover crop; crop residue; soil characterization